Expression of CD70 in nasal natural killer/T cell lymphoma cell lines and patients; its role for cell proliferation through binding to soluble CD27. (4th December 2012) - Yoshino, Kazumi; Kishibe, Kan; Nagato, Toshihiro; Ueda, Seigo; Komabayashi, Yuki; Takahara, Miki; Harabuchi, Yasuaki
Summary Nasal natural killer (NK)/T cell lymphoma (NNKTL) is associated with Epstein–Barr virus (EBV). The present study analysed gene expression patterns of the NNKTL cell lines SNK6, SNK1 and SNT8, which are positive for EBV and latent membrane protein (LMP)‐1, using a complementary DNA array analysis. We found that CD70 was specifically expressed in SNK6 and SNT8. Reverse transcription polymerase chain reaction and flow cytometric analyses confirmed that CD70 was expressed in all 3 NNKTL cell lines, but not in the other EBV‐positive NK‐cell lines. In vitro studies showed that NNKTL cell lines proliferated, in a dose‐dependent fashion, in response to exogenous soluble CD27, which is the ligand for CD70. In NNKTL patients, we confirmed that the CD70 was expressed on the lymphoma cells in NNKTL tissues and that soluble CD27 was present in sera at higher levels as compared to healthy individuals. Finally, complement‐dependent cytotoxicity assay showed that anti‐CD70 antibody mediated effective complement‐dependent killing of NNKTL cells and the affected target CD70 expression on the cells. These results suggest that CD70 acts as a functional receptor binding to soluble CD27, resulting in lymphoma progression and that immunotherapy using anti‐CD70 antibody may be a potential candidate for treatment for NNKTL.